Study of Spiritual Tourism Areas - Healing in Cirebon - Agustina, I H; Fauzi, H; Ekasari, A M (KnE Social Sciences, 2023)
Today, spiritual tourism, an alternative form of travel, is becoming increasingly common. Spirituality is now seen as a lifestyle, particularly when it comes to attaining a balance between the mind, body, and soul, which is often referred to as spiritual healing. People seek new meaning and fulfilment through spiritual healing, fulfilling their need for security in the process. Cirebon’s tourism locations embrace the esoteric tradition and offer spiritual healing practices. This study aims to describe spiritual healing in Cirebon’s tourism activities. The research adopts an exploratory method, and data are collected through surveys and field observations. The survey data is then processed and analysed by categorising the responses. The information is grouped according to similarities, and then examined and interpreted in the context of Cirebon’s spiritual tourism sector. The selected participants for this study are individuals who have engaged in spiritual tourism in Cirebon on multiple occasions. The study’s findings provide valuable insights for the development of spiritual healing in Cirebon. The results can be utilised to further explore the potential of spiritual healing tourism in Cirebon, benefiting its overall tourism industry. Keywords: area, Cirebon-esoteric-tradition, explorative, spiritual-healingToday, spiritual tourism, an alternative form of travel, is becoming increasingly common. Spirituality is now seen as a lifestyle, particularly when it comes to attaining a balance between the mind, body, and soul, which is often referred to as spiritual healing. People seek new meaning and fulfilment through spiritual healing, fulfilling their need for security in the process. Cirebon’s tourism locations embrace the esoteric tradition and offer spiritual healing practices. This study aims to describe spiritual healing in Cirebon’s tourism activities. The research adopts an exploratory method, and data are collected through surveys and field observations. The survey data is then processed and analysed by categorising the responses. The information is grouped according to similarities, and then examined and interpreted in the context of Cirebon’s spiritual tourism sector. The selected participants for this study are individuals who have engaged in spiritual tourism in Cirebon on multiple occasions. The study’s findings provide valuable insights for the development of spiritual healing in Cirebon. The results can be utilised to further explore the potential of spiritual healing tourism in Cirebon, benefiting its overall tourism industry. Keywords: area, Cirebon-esoteric-tradition, explorative, spiritual-healing